2001
DOI: 10.1182/blood.v98.8.2332
|View full text |Cite
|
Sign up to set email alerts
|

Standardized, unrelated donor cord blood transplantation in adults with hematologic malignancies

Abstract: The potential role of unrelated donor cord blood transplantation (UD-CBT) in adults remains unclear. This study reports the results of UD-CBT in 22 adults with hematologic malignancies following conditioning with thiotepa, busulfan, cyclophosphamide, and antithymocyte globulin in 21, with thiotepa, fludarabine, and antithymocyte globulin in 1, and graft-versus-host disease (GVHD) prophylaxis with cyclosporine and prednisone. Median age was 29 years (range, 18-46 years), and median weight was 69.5 kg (range, 41… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
163
1
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(178 citation statements)
references
References 35 publications
9
163
1
1
Order By: Relevance
“…On the other hand, previously published literature pointed to infection as a major cause of death. 10,14,25 Despite a high frequency of HLA-mismatched grafts and faster tapering of GVHD prophylactic immunosuppressants in the CBT group, the risk of developing acute GVHD was lower than that in the BMT group, which was significant for grades III and IV severe acute GVHD, as described in other reports. 12,26 The lower incidences of acute GVHD in both BM transplant and CB transplant recipients in our series compared with other reports could be correlated to the higher frequency of the gene that induces higher interleukin-10 production in the Japanese population 27 or are assumed to reflect a lower degree of diversity for HLA and minor histocompatibility antigens among Japanese.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…On the other hand, previously published literature pointed to infection as a major cause of death. 10,14,25 Despite a high frequency of HLA-mismatched grafts and faster tapering of GVHD prophylactic immunosuppressants in the CBT group, the risk of developing acute GVHD was lower than that in the BMT group, which was significant for grades III and IV severe acute GVHD, as described in other reports. 12,26 The lower incidences of acute GVHD in both BM transplant and CB transplant recipients in our series compared with other reports could be correlated to the higher frequency of the gene that induces higher interleukin-10 production in the Japanese population 27 or are assumed to reflect a lower degree of diversity for HLA and minor histocompatibility antigens among Japanese.…”
Section: Discussionsupporting
confidence: 55%
“…[1][2][3] While cord blood cells have been increasingly used as a source of hematopoietic stem cells for allogeneic transplantation, most recipients were pediatric [4][5][6][7][8] because of the relatively lower cell doses in cord blood grafts. [4][5][6][7][8] Recently, multicenter and single-center studies of unrelated cord blood transplantation (CBT) in adults after myeloablative 9,10 or nonmyeloablative 11 conditioning regimens showed cord blood could effectively restore hematopoiesis and was associated with acceptable levels of graft-versus-host disease (GVHD). There have also been 2 clinical comparisons of CBT and bone marrow transplantation (BMT) from unrelated donors: one a multicenter study of acute leukemia 12 and the other a single-institution matched-pair analysis.…”
Section: Introductionmentioning
confidence: 99%
“…UCB is enriched with haematopoietic progenitor cells and contains sufficient numbers of HSCs to reconstitute most paediatric patients. 1,2,4,6,8,9,17,19,[26][27][28][29][30][31][32][33] Most studies have shown that the nucleated cell dose is of paramount importance for haematopoietic recovery, 2,4,6,14,16,17 Wagner et al 10 have also shown the CD34 cell dose as being a significant variable not only for haematopoietic recovery but also for survival. The importance of CD34 cell dose has been replicated in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…2,10,11,21,23,34,36 TRM in adult recipients of UCB after a myeloablative regimen has been reported to be as high as 60%. 7,10,14,17,19,[30][31][32][33] Comparing UCBT to BMT, Rocha et al 22 compared the outcomes of 541 children transplanted for the treatment of acute leukaemia receiving a UCBT (n ¼ 99), unmanipulated BMT (n ¼ 262), or T-cell-depleted BMT (n ¼ 180). UCB recipients were observed to have a higher TRM within the early period after transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of the early successes with pediatric cord blood transplantation (CBT), cord blood from unrelated donors has been increasingly used as an alternative stem cell source for adult patients with hematological malignancies. [1][2][3][4][5][6][7][8][9][10][11][12][13] Recently several reviews including the clinical results of adult CBT have been published. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] In this review, we focus on recent results of myeloablative CBT in adults.…”
Section: Introductionmentioning
confidence: 99%